The Priorities of Policy Making for Health Promotion Behaviors of Female Workers: A Sequential Mixed Method Study - Zohre Keshavarz; Masoumeh Simbar; Ali Ramezankhani; Abolghasem Pourreza; Hamid Alavi Majd (Tehran University of Medical Sciences, 2016)
Background and Aim: Caring about workers is important due to protect human capital and economic growth. Understanding health priorities is one of the main challenges of health management. The aim of this research was to priorities health promotion behaviors of female workers. Materials and Methods: This study was conducted in 2012 and had a triangulation design with sequential qualitative-quantitative method based on "integrated model of planned behavior and self-efficacy". In the qualitative phase of the study, a content analysis approach was done  to develop the questionnaire, based on the model and psychometric properties were assessed. Then, the educational intervention was conducted in an experimental study with randomized sampling in 70 female workers (35 intervention group, 35 controls). The pretest and posttest was compared. Results: Content analysis demonstrated 6 main themes, including the main constructs of the research model: attitude, subjective norm, perceived behavioural control, self-efficacy, intention and behaviour in 4 domain (nutrition, exercise, cervical and breast cancer screening, cope with stress). Scale level content validity index was 0.93. Confirmatory factor analysis showed CFI=0.97, GFI=0.95, IFI=0.96, NNFI=0.98, NFI=0.97, RMSEA=0.05. Concurrent validity versus the Health-promoting lifestyle profile II showed r=0.60. Cronbach alpha was 0.75-0.93 across the subscales. Test-retest reliability revealed no significant differences.After educational intervention there was a significant increase in attitude, subjective norm, perceived behavioral control, self-efficacy, intention and behavior of female workers in intervention group. Also, effect of intervention program was mostly in self-efficacy construct. Conclusion: With regards to working conditions economic and socio-cultural barriers in female workers, health policy making is essential in this group to promote health